2022
DOI: 10.1002/ecs2.4065
|View full text |Cite
|
Sign up to set email alerts
|

Whole plant traits of coastal dune vegetation and implications for interactions with dune dynamics

Abstract: Coastal dunes are important protective features against sea level rise and coastal storms. Interactions between dune plant aboveground structures and sediment trapping that allow for dune building and maintenance are well established. More recently, studies documenting belowground biomass for promoting erosion resistance in dominant dune species have been conducted, yet a knowledge gap remains regarding species-specific characterization of whole plants, specifically with respect to roots, rhizomes, and belowgr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 73 publications
0
10
0
Order By: Relevance
“…Two decades prior, dunes on Hog were dominated by Ammophila and Spartina , with Panicum only comprising ~ 2% of dune relative cover 37 . By 2022 Panicum relative cover increased to > 40% on both Hog and Metompkin which has implications for overall dune structure as Panicum exhibits phalanx growth due to shorter rhizomes 39 and traps 50% less sediment than Ammophila or Spartina , forming smaller, hummocky dunes. Panicum has the potential to alter dune dynamics and growth from those previously documented in Virginia, creating new climate-vegetation scenarios that current models may not predict.…”
Section: Discussionmentioning
confidence: 99%
“…Two decades prior, dunes on Hog were dominated by Ammophila and Spartina , with Panicum only comprising ~ 2% of dune relative cover 37 . By 2022 Panicum relative cover increased to > 40% on both Hog and Metompkin which has implications for overall dune structure as Panicum exhibits phalanx growth due to shorter rhizomes 39 and traps 50% less sediment than Ammophila or Spartina , forming smaller, hummocky dunes. Panicum has the potential to alter dune dynamics and growth from those previously documented in Virginia, creating new climate-vegetation scenarios that current models may not predict.…”
Section: Discussionmentioning
confidence: 99%
“…Planting supplemental stabilizing plant growth forms may act synergistically with dune grasses to facilitate positive interactions, such as by providing additional sediment stabilization via rhizomes, sand trapping, and soil nutrients (Brown, Zinnert, and Young, 2018). Different plant growth forms and varied plant functional traits lead to a diversity of functional roles served in coastal vegetation communities and emergent interactions (Brown, Zinnert, and Young, 2018; Walker and Zinnert, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Recent work has also shown that functionally similar species, such as A. breviligulata and U. paniculata , have different strategies for surviving the dune environment, as evidenced by differences in plant functional traits. For instance, Walker and Zinnert (2022) found that while both A. breviligulata and U. paniculata had similar belowground biomass, they displayed markedly different root traits. Meanwhile, Spartina patens (salt hay), recently renamed Sporobolus pumilus (Peterson et al ., 2014), and Panicum amarum (bitter panicum) were 70% less massive underground despite serving similar functional roles as dune builders.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dune nourishment region initially included regular spacing of sprigs Ammophila brevigulata , with additional Uniola paniculata planted near the dune crest (CPE, 2017), with similar vegetation present in the other partially managed coastal sections as well. Conversely, there is a wider range of species present at the unmanaged FRF site including Panicum amarum , Spartina patens , Solidago sempervirens , Erigeron canadensis , and Smilax bona‐nox (e.g., Levy, 1976; Walker & Zinnert, 2022). Quadrat surveys of dune grass vegetation on the dune face in portions of the study site, as presented in White (2022), showed that the total living cover was about twice as high in Zone 2 than Zone 3 and that the species richness was higher in Zone 2 than Zone 3.…”
Section: Discussionmentioning
confidence: 99%